Humanising coursebook dialogues. Issue 2 (3rd May 2016) - Timmis, Ivor
ABSTRACT: In this article, I argue that the most important thing about coursebook dialogues is not whether they are 'authentic' or 'inauthentic' but whether they are plausible as human interaction and behaviour. Coursebook dialogues are often constructed as vehicles for various kinds of language work and even sometimes as vehicles for socio-political messages [Mukundan, J. 2008. "Agendas of the State in Developing World English Language Textbooks." Folio 12 (2): 17–19.]. As a result, smiles are abundant, problems are few, and reality rare in the world of the coursebook dialogue [Carter, R. 1998. "Orders of Reality: CANCODE, Communication and Culture." ELT Journal 52 (1): 43–56; Cook, V. 2013. "Materials for Adult Beginners from an L2 User Perspective." In Developing Materials for Language Teaching, edited by B. Tomlinson, 289–309. London: Bloomsbury]. In this article, I suggest how we can humanise the coursebook [Tomlinson, B. 2013. "Humanising the Coursebook." In Developing Materials for Language Teaching, edited by B. Tomlinson, 162–174. London: Bloomsbury] through some relatively minor adaptations to dialogues based on processes such as: (1) extending the dialogue, (2) changing the register, (3) changing the cast of characters, (4) changing the mood, (5) changing the 'plot', and (6) 'unscripting' the dialogue. Applying such processes, I argue, potentially brings a number of benefits. These benefits include 'varied repetition' [Maley, A. 1994. "Play It Again, Sam: A Role for Repetition." Folio 1 (2): 4–5]; intensive listening practice; sensitisation to differences between scripted and 'authentic' speech; scope for creativity and humour. The longer-term benefit of such an approach, I argue, is that it develops the important habit of noticing.